2017
DOI: 10.1111/1467-8268.12235
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Environment and Microfinance Performance in Sub‐Saharan Africa

Abstract: This paper explores the impact of the institutional environment on the performance of 291 microfinance institutions in 34 sub‐Saharan Africa countries during the period 2006 to 2014, by analysing the unbalanced panel data using fixed effects and generalized method of moments (GMM) estimation techniques. The panel regression results demonstrate strong evidence that a strong institutional environment has a positive effect on the performance of microfinance institutions in sub‐Saharan Africa. More specifically, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…On a closely related issue, Daher and Le Sahout () stress the importance of strong property rights and low levels of government interference in financial markets. Chikalipa () finds a positive relationship between the lack of rules constraining business and MFI performance in sub‐Saharan Africa. Finally, Barry and Tacneng () argue that the link between institutional quality and MFI performance depends on the type of MFI.…”
Section: Discussionmentioning
confidence: 99%
“…On a closely related issue, Daher and Le Sahout () stress the importance of strong property rights and low levels of government interference in financial markets. Chikalipa () finds a positive relationship between the lack of rules constraining business and MFI performance in sub‐Saharan Africa. Finally, Barry and Tacneng () argue that the link between institutional quality and MFI performance depends on the type of MFI.…”
Section: Discussionmentioning
confidence: 99%
“…The main results reported in Table used ROA as a dependent variable, yet we experiment with applying the ROE as a profitability measure. The adoption of ROE as an alternative profitability measure is a widely used approach in a number of empirical studies in both the microfinance and traditional banking industries (see Chikalipah, ; Dietrich & Wanzenried, ). Table presents the results of estimating Equation using the ROE as a dependent variable.…”
Section: Additional Results and Robustness Checksmentioning
confidence: 99%
“…The exact opposite results were reported by Batra (), who found a limited contribution of branch expansion to the bank profitability in India, whilst Ikhide () demonstrated that the extension of the branch offices of commercial banks to rural areas could help attenuate the poor savings performance in most African economies. On the other side, there is a growing plethora of empirical studies in the microfinance industry, which indicates that serving more customers augment the profitability of MFIs (see Abate, Borzaga, & Getnet, ; Adhikary & Papachristou, ; Chikalipah, ; Cull, Demirgu¨ç‐Kunt, & Morduch, ; Hermes & Lensink, ; Hermes, Lensink, & Aljar, ; Kumar Kar, ; Quayes, ).…”
Section: Related Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Environmental Sustainability Index (ESI) is a composite index that tracks a variety of socio-economic, environmental, and institutional indicators that characterize and influence environmental sustainability at the national level. Given these reasons and concerns from the previous literature review in this context, such as the studies of Echavarren (2017), Jamali et al (2017), and Chikalipah (2017). Our contribution tries to answer the question of the impact of environmental performance on sustainable development.…”
Section: Introductionmentioning
confidence: 96%